A consideration of the usefulness of Medard Boss's approach to dream explication, in an attempt to reveal the potential for forward movement - Hill, Patricia Margaret (Rhodes University, Faculty of Humanities, Department of Psychology, 1992)
The purpose of this study is to investigate the value of using a Daseinsanalytic approach to dream explication in order to reveal the essential meaningfulness of behaviourial possibilities for the patient. After discussing the Daseinsanalytic view on dream explication, emphasizing Medard Boss's approach as the major exponent of this view, the study explores the usefulness and validity of the study as a method of investigating the dreams from this perspective. The dreams related in this study are examined individually, giving a phenomenological understanding of each and also providing a possible prospective focus for therapy. It will be shown that the phenomenological understanding of the patient's dreams corresponds with his subjective experience of his emotional existential situation and that any positive changes in the content of the dreams over time corresponds with observable and related changes in his behaviour, ideation and mood. However, if the suggested prospective focus of Medard Boss had been more usefully employed when each dream was explicated in the therapy sessions, it is felt that the progress of therapy would have been greatly enhanced. This study therefore concludes that the use of Medard Boss's approach to dream explication has not only a hermeneutic value in the process of therapy, but also aids the dreamer in becoming aware of the possible modes of behaviour yet unrevealed in his waking life.
Keywords: Boss, Medard, 1903-1990; Dream interpretation -- Case studies